Bioinformatics study of the a222v substitution in sars-cov-2 spike protein - Ariesaka, Kiky Martha; Nuryady, Moh Mirza; Rini, Ika Agus (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2025)
COVID-19, caused by SARS-CoV-2, has infected over 200 million people and caused 4.3 million deaths globally, with over 3.7 million cases and 110,000 deaths in Indonesia. SARS-CoV-2, a single-stranded RNA virus, has a genome encoding proteins such as Spike (S), Envelope (E), Membrane (M), and Nucleocapsid (N). The S protein, comprising S1 and S2 domains, facilitates ACE2 receptor binding and membrane fusion. This study examines the phylogenetic relationship of the A222V substitution in the S protein with various global isolates. We collected 25 complete SARS-CoV-2 sequences from the GISAID database, performed multiple sequence alignments using Clustal W in MEGA-X software, and constructed phylogenetic trees using the neighbor-joining method. The urgency of this paper lies in understanding the impact of the A222V mutation on the virus's infectivity and spread, which is crucial for developing targeted treatments and vaccines. The A222V variant, first identified in Spain in summer 2020, has spread rapidly across Europe, raising concerns about its potential to increase transmissibility or affect vaccine efficacy. The A222V variant likely affects protein conformation or stability rather than receptor binding or membrane fusion. Understanding these changes is essential as it can influence the virus's behavior and efficacy of public health interventions. The study found high mutation rates in the S gene with diverse point mutations. Phylogenetic analysis revealed that A222V isolates clustered closely with D614G variants. In conclusion, not all mutations result in amino acid changes, and A222V has minimal impact on ACE2 binding but may influence protein stability.